Quantifying macroeconomic uncertainty in Norway - Frida Bowe; Sara Jahr Kirkeby; Ingvild Hagen Lindalen; Kristine Aunvåg Matsen; Sara Skjeggestad Meyer; Ørjan Robstad (Norges Bank, 2023)
This paper presents a framework for quantifying uncertainty around point forecasts for GDP, inflation and house prices in Norway. The framework combines quantile regressions using a broad set of uncertainty indicators with a skewed t-distribution, allowing for time-variation and asymmetry in the uncertainty forecasts. This approach helps provide deeper insights into the macroeconomic uncertainty surrounding forecasts than more traditional time-series models, where uncertainty is usually symmetric and with limited time-variation. Formal tests, such as the log score and the Continuous Ranked Probability Score (CRPS), show that using informative indicators tend to improve density forecasts, particularity in the medium run.
hdl:11250/3073130
Keywords: C53; E23; E27; E3; E44; 330; GDP; house prices; inflation; forecasting; quantile regressions; Growth-at-risk; Houseprices-at-risk; Inflation-at-risk; density forecast; fan charts